Suppressive Role of Tissue Factor Pathway Inhibitor-α in Platelet-Dependent Fibrin Formation under Flow Is Restricted to Low Procoagulant Strength - Thomassen, Stella; Mastenbroek, Tom G.; Swieringa, Frauke; Winckers, Kristien; Feijge, Marion A.H.; Schrijver, Roy; Cosemans, Judith M.E.M.; Maroney, Susan A.; Mast, Alan E.; Hackeng, Tilman M.; Heemskerk, Johan W.M. (Thrombosis and Haemostasis, 2018)
Tissue factor pathway inhibitor-alpha (TFPI-α) is a Kunitz-type serine protease inhibitor, which suppresses coagulation by inhibiting the tissue factor (TF)/factor VIIa complex as well as factor Xa. In static plasma-phospholipid systems, TFPI-α thus suppresses both factor Xa and thrombin generation. In this article, we used a microfluidics approach to investigate how TFPI-α regulates fibrin clot formation in platelet thrombi at low wall shear rate. We therefore hypothesized that the anticoagulant effect of TFPI-α in plasma is a function of the local procoagulant strength—defined as the magnitude of thrombin generation under flow, due to local activities of TF/factor VIIa and factor Xa. To test this hypothesis, we modulated local coagulation by microspot coating of flow channels with 0 to 100 pM TF/collagen, or by using blood from patients with haemophilia A or B. For blood or plasma from healthy subjects, blocking of TFPI-α enhanced fibrin formation, extending from a platelet thrombus, under flow only at <2 pM coated TF. This enhancement was paralleled by an increased thrombin generation. For mouse plasma, genetic deficiency in TFPI enhanced fibrin formation under flow also at 0 pM TF microspots. On the other hand, using blood from haemophilia A or B patients, TFPI-α antagonism markedly enhanced fibrin formation at microspots with up to 100 pM coated TF. We conclude that, under flow, TFPI-α is capable to antagonize fibrin formation in a manner dependent on and restricted by local TF/factor VIIa and factor Xa activities.
Keywords: fibrin clot formation; haemophilia; mouse; platelets; TFPI; thrombin generation